Detection of Epstein-Barr genome in the lymph nodes of Hodgkin's disease. - Bellas, C. (BMJ Group, 1993)
We have used the enzymatic in situ hybridization method to investigate the presence of Epstein-Barr virus (EBV) genome in lymph node tissues from patients with Hodgkin's disease. Also, 11 patients with persistent human immuno-deficiency virus-associated generalized lymphadenopathy as well as seven autopsy cases with no Hodgkin's disease, formed part of these studies. EBV DNA-positive reaction was demonstrated in Reed-Sternberg cells and variants in seven of 16 cases and in the small accompanying lymphocyte cell population in 14 of the 16 cases. It was also found in eight of the 11 cases with persistent generalized lymphadenopathy but in none of the lymph nodes from negative selective autopsy cases. Our results indicate that the colorimetric in situ hybridization technique is useful in EBV nucleic acid detection and cell-type localization in Hodgkin's disease. Additionally, the detection of EBV genome, not only in the diagnostic cells but in the small lymphocyte cell components, could provide new insights into the potential role of this agent in the pathogenesis of Hodgkin's disease.